Data-Driven PID Tuning Based on Safe Experimentation Dynamics for Control of Liquid Slosh - Nor Sakinah, Abdul Shukor; Mohd Ashraf, Ahmad; Mohd Zaidi, Mohd Tumari (IEEE, 2017)
An introductory research about a data-driven PID tuning for the control of liquid slosh system based on Safe Experimentation Dynamics (SED) is presented in this paper. A performance comparison between the SED and Simultaneous Perturbation Stochastic Approximation (SPSA) based method for data-driven PID tuning is observed and discussed. The performance is evaluated by numerical examples in terms of tracking performance, control input energy and computation time. The simulation results demonstrated that SED based data driven PID successfully reduced the liquid slosh whilst the desired position of the cart is achieved. In addition, smaller control input energy is used.